Genetic Polymorphism of Inflammation Response Genes TNF-α -308G > A and IL-8 -251 T>A and their Influence on Colorectal Cancer Predisposition Risk in Malaysian Population. - Mohd Aminudin, Mustapha; Siti Nurfatimah, Mohd Shahpudin; Ahmad Aizat, Abdul Aziz; Venkatesh R, Naik; Biswal, Mohan Biswal; Zaidi, Zakaria; Shanwani, A.; Mohammad Radzi, A.H.; Ankathil, Ravindran (John Wiley & Sons, Inc, 2010)
Introduction Genes encoding xenobiotic metabolizing enzymes especially CYP1A2 play an important role in determining the out come of carcinogen exposure and Colorectal Cancer susceptibility risk. Functional polymorphisms of G3860A, T739G and C729T of CYP1A2 gene have been identified.